Abelhas visitantes florais e potenciais polinizadoras do café (Coffea arabica L.) ecológico e sombreado no Maciço de Baturité - Ceará - Carvalho Neto, Francisco Humberto de (2010)
The survey was conducted on the farm São Sebastião, located in the city of Mulungu - CE. Data were collected and studied during the period November 2009 to June 2010 with the aim of studying the floral visitors and pollination of coffee (Coffea arabica L.) and green shade of Mundo Novo and Maragogipe. We studied the floral biology and pollination requirements of the cultivars, the grazing behavior and evaluation of fruit after 100 days of pollination. The results showed that Apis mellifera was the most frequent in the flowers (9 ± 0.42, n = 455) followed by Trigona fulviventris (4 ± 0.52, n = 206), Melipona rufiventris (4 ± 0.42, n = 151), Nannotrigona sp. (3 ± 0.48, n = 148), Trigona spinipes (3 ± 0.43, n = 157) and Xylocopa grisescens (2 ± 0.78, n = 38). After 100 days of pollination (open pollination, with narrow paper bag, with narrow organza bag, manual cross-pollination and geitonogamy) showed significant differences (Mundo Novo X2 = 44.9495, DF=4,p<0.005; Maragogipe: X2 = 59.8649, df = 4, p <0.005) between treatments with respect to viable fruits. The open pollinated differed significantly (P <0.05) of all treatments for Mundo Novo. In the cultivar Maragogipe, the free pollination, manual cross-pollination and geitonogamy presented the highest number of viable fruits and did not differ. However, these treatments differed significantly (P <0.05) than treatment with restricted pollination bag and this in turn also differed from the restricted pollination treatment with organza bag. The total weight of 100 days after the pollination treatments showed no significant differences between cultivars at a significance level of 5%. It is concluded that the Arabic coffee can produce fruits under any circumstances tested. Despite being selfcompatible, also supports the cross-pollination that leads to an increase in productivity. The wind and gravity did not favor an increase in fruit set fruit. Species Apis mellifera, Melipona rufiventris and Xylocopa grisescens recorded behavior of potential pollinators.